2008
DOI: 10.5194/acp-8-4517-2008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of OMI ozone and UV irradiance data with ground-based measurements at two French sites

Abstract: Abstract. Ozone Monitoring Instrument (OMI), launched in July 2004, is dedicated to the monitoring of the Earth's ozone, air quality and climate. OMI is the successor of the Total Ozone Mapping Spectrometer (TOMS) instruments and provides among other atmospheric and radiometric quantities the total column of ozone (TOC), the surface ultraviolet (UV) irradiance at several wavelengths, the erythemal dose rates and the erythemal daily doses. The main objective of this work is to compare OMI data with data from gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
63
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 25 publications
10
63
0
2
Order By: Relevance
“…The set of values with AOD(440 nm) > 0.25 and α ≥ 0.82 is shown as red points. The relationship between OMI-Brewer differences and AOD at 340 nm presents a great variability, depending on the site or aerosol type (e.g., Kazantzidis et al, 2006;Ialongo et al, 2008;Buchard et al, 2008). Antón et al (2007) found a better correlation for binned data, showing clearly that the OMI bias increases as the AOD increase.…”
Section: Absorbing Aerosol Determination Based On Aod-alpha and Ai Inmentioning
confidence: 95%
See 1 more Smart Citation
“…The set of values with AOD(440 nm) > 0.25 and α ≥ 0.82 is shown as red points. The relationship between OMI-Brewer differences and AOD at 340 nm presents a great variability, depending on the site or aerosol type (e.g., Kazantzidis et al, 2006;Ialongo et al, 2008;Buchard et al, 2008). Antón et al (2007) found a better correlation for binned data, showing clearly that the OMI bias increases as the AOD increase.…”
Section: Absorbing Aerosol Determination Based On Aod-alpha and Ai Inmentioning
confidence: 95%
“…Recent publications on OMI operational UV validation have been carried out by Buchard et al (2008), Ialongo et al (2008) and Weihs et al (2008) at different European locations but no aerosol corrections were made. More recently, the works of Kazadzis et al (2009), Arola et al (2009) and Ialongo et al (2010) have applied the aerosol absorption correction suggested earlier in Krotkov et al (2005) and Arola et al (2005).…”
Section: Introductionmentioning
confidence: 99%
“…Intercomparisons were also done with the UV radiation measured in two French sites: Villeneuve d'Ascq and Briançon (Buchard et al, 2008). Comparisons of the erythemal dose rates and erythemal daily doses for clear sky show that OMI overestimates surface UV doses at Villeneuve d'Ascq by about 13 % and that on all sky conditions, the bias slightly increases.…”
Section: Aura/omimentioning
confidence: 99%
“…However, validation exercises are difficult to achieve due to differences in temporal and spatial resolutions of GB and SB data products. Extensive comparison studies between surface UV provided by OMI and GB measurements have been previously made (Tanskanen et al, 2007;Buchard et al, 2008;Ialongo et al, 2008;Weihs et al, 2008). Those studies dealt with version 1.2, which did not account for the influence of absorbing aerosols, implying a positive bias in OMI product.…”
Section: Introductionmentioning
confidence: 99%